Guilty pleas in international criminal law: constructing a restorative justice approach - Combs, Nancy Amoury (Stanford Univ. Press, 2007)
International criminal justice then and now : the long road from impunity to [some] accountability --- Financial realities : targeting only the leaders -- Do the numbers count? : the ends served by International criminal prosecutions in societies emerging from mass atrocities -- The plea bargaining of international crimes : the practice of the ICTY, ICTR, special panels for East Timor, and Gacaca Courts -- Plea bargaining at the ICTR and at the special panels in East Timor -- Using conventional plea bargaining to increase the number of criminal prosecutions for international crimes -- Plea bargaining as restorative justice : using guilty pleas to advance both criminal accountability and reconciliation -- Applying restorative principles in the aftermath of different atrocities : a contextual approach -- The minimal role of restorative justice in current international criminal prosecutions